Analisis Socio-legal Perlindungan Ekspresi Budaya Tradisional Perang Ketupat di Kecamatan Tempilang, Bangka Barat - Hariansah, Syafri (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 4 (2024)DO - 10.24843/JMHU.2024.v13.i04.p06, 2024)
This research endeavors to analyze the safeguarding of the traditional cultural expression of the “perang ketupat” as a communal intellectual property in Tempilang District, West Bangka, as well as to explore the perception of the Air Lintang community in Tempilang District towards efforts to protect the “perang ketupat” tradition as communal intellectual property. This study employs a socio-legal approach through combining qualitative analysis and a simple quantitative survey. Qualitative analysis is carried out to understand the social context, cultural values, and community perspectives in managing communal intellectual rights. The quantitative survey involved 110 respondents from 11 neighborhood units in Air Lintang village to measure community perceptions about legal protection of the “perang ketupat” tradition. The results show that although the Tempilang community consistently preserves the “perang ketupat” tradition, their grasp of intellectual property rights and the corresponding legal safeguards remains underdeveloped.  Most respondents acknowledge the significance of safeguarding traditional cultural expressions using legal instruments, However, most respondents have an incomplete understanding the implications of registering the “perang ketupat” as communal intellectual property. This research encourages strengthening community legal awareness through legal literacy programs involving collaboration between the government, local governments, and universities.